Pengaruh Faktor-Faktor Kualitas Pelayanan Bandara terhadap Kepuasan Penumpang Selama Berada di Bandara Internasional Soekarno-Hatta - Nungky Puspita; Lukman Hakim (Fakultas Pariwisata Universitas Pancasila, 2013)
This study aims to investigate the effect of service quality on passengers’ satisfaction at the Soekarno-Hatta International Airport. The method used is multiple regression analysis to examine the effect of servicescape, service personnel and service providers on passengers' satisfaction. Primary data was gathered from 100 respondents who filled the questionnaires while waiting for their flights at the Soekarno-Hatta International Airport. The results of this study showed that spatial layout and functionality, as well as attititude and expertise significantly influence passengers' satisfaction. In addition, other factors namely maintenance and leisure also have significant effect on passengers' satisfaction.